Emergency cholecystectomy with an intraoperative hemobilia diagnosis: case report - Ruiz, Christian (2022)
Hemobilia (HB) is the presence of blood in or through the biliary tract. Its most common causes are iatrogenic, traumatic, neoplasms, and cholangiovenous or arterio-biliary fistulas. Also, gallstones account for 5-15% of such cases. We present the case of a 28-year-old woman, with no remarkable history or anticoagulant use, who was initially diagnosed with acute cholecystitis, and required emergency open cholecystectomy. During the operation, a clot adhered to the gallbladder lumen and two calculi were evidenced. The diagnosis was confirmed with histopathological findings. Due to its clinical similarity, HB should be considered in patients with a history of anticoagulant therapy, trauma, malignancy, or with findings consistent with alithiasic cholecystitis. HB may also occur in patients with no remarkable history, and it be associated with cholelithiasis. Treatment depends on the patient’s hemodynamic status and etiology. Surgery is required in cholecystitis, because of its high mortality rate and occurrence of gallbladder perforation (2-15%).